1982
DOI: 10.1063/1.331456
|View full text |Cite
|
Sign up to set email alerts
|

Properties of CdTe-Te alloy films prepared using molecular beams

Abstract: A series of CdTe-Te alloy films was prepared by molecular beam deposition in an ultrahigh vacuum. This allowed precise and systematic variation of the Cd/Te vapor flux ratio during growth which produced films whose resistivity varied by more than eleven orders of magnitude. The electrical, structural, chemical, optical, and surface properties of these CdTe-Te alloy films are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The growth of compound thin films from component molecular beams has been described by many investigators (Gunther, 1968;Smith and Pickhardt, 1975;Faurie et al, 1983Faurie et al, , 1985Chow and Johnson, 1985;Jansen and Melnyk, 1984;Foxon, 1983;Kawabe and Matsiura, 1984;Myers et al, 1982;Summers et al, 1984) with general agreement that the conversion or utilization of one species and the film composition vary with the substrate temperature and flux of the other components. A simplified description of the generally accepted mechanisms that explain this behavior follows.…”
Section: Thicknessmonitormentioning
confidence: 99%
“…The growth of compound thin films from component molecular beams has been described by many investigators (Gunther, 1968;Smith and Pickhardt, 1975;Faurie et al, 1983Faurie et al, , 1985Chow and Johnson, 1985;Jansen and Melnyk, 1984;Foxon, 1983;Kawabe and Matsiura, 1984;Myers et al, 1982;Summers et al, 1984) with general agreement that the conversion or utilization of one species and the film composition vary with the substrate temperature and flux of the other components. A simplified description of the generally accepted mechanisms that explain this behavior follows.…”
Section: Thicknessmonitormentioning
confidence: 99%
“…Britt and Ferekides [6] have reported a CdTe/CdS solar cell with an efficiency of 16.8%. Due to its low sublimation temperature, CdTe polycrystalline films can be prepared by several techniques [7][8][9][10][11][12][13]. The close spaced sublimation (CSS) technique is one of the various techniques that have produced encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [10] have reported on a CdTe/CdS solar cell with an efficiency of 16.5%. Because of its low sublimation temperature, CdTe polycrystalline films can be prepared by several techniques, such as thermal evaporation [11], metal organic chemical vapour deposition (MOCVD) [12], radio frequency (RF) sputtering [13], closed space sublimation (CSS) [14], screen printing [15], hotwall flash evaporation [16], molecular beam deposition [17,18], hot-wall vacuum evaporation [19][20][21], etc. The CSS technique is one of the various techniques that have produced encouraging results.…”
Section: Introductionmentioning
confidence: 99%